DO OVERCONFIDENT INVESTORS TRADE EXCESSIVELY IN THE CAPITAL MARKET? EVIDENCES IN AN EXPERIMENTAL RESEARCH SETTING - Mahatma Kufepaksi (Journal of Indonesian Economy and Business (JIEB), 2011)
The existence of overconfident investors in capital markets has been the subject of much researches in the past. Using the market data, these previous researches demonstrates that overconfident investors tend to trade excessively, leading to losses. The current experimental research addresses these issues in the Indonesia Capital Market. According to its methodology, participants are classified into three groups based on their score of overconfidence: moderate, more overconfident, and less overconfident investors. The research design employs the state of no available market information, good news signals, and bad news signals as treatments. The result demonstrates that the more overconfident investors perform higher trading value than those who are less overconfident in all artificialmarkets leading to transaction losses, except that in the bad news market. In that bad news market, the more and the less overconfident investors gain profits, and the moderateinvestors suffer from trading losses.Keywords: overconfidence, excessive trading, profit and loss